Особливості застосування технології спільного викладання в інклюзивному освітньому середовищі - Васильєва Галина; Vasylieva Halyna; Мартинчук Олена; Martynchuk Olena; Фень Марія; Fen Mariia (Видавництво «Код», 2025)
Резюме. Стаття присвячена теоретичному та практичному дослідженню впровадження технології спільного викладання в контексті навчання учнів з особливими освітніми потребами (ООП). На основі аналізу зарубіжного практичного досвіду застосування цієї технології виокремлено та охарактеризовано шість найбільш поширених моделей співвикладання, а також висвітлено особливості впровадження технології спільного викладання в закладах освіти Польщі та Фінляндії.

Abstract. The article examines the theoretical foundations and practical implementation of co-teaching in the education of students with special educational needs (SEN). Based on the analysis of international practical experience with this technology, six of the most common co-teaching models have been identified and characterized, and the features of implementing co-teaching in educational institutions in Poland and Finland have also been highlighted. The author found that co-teaching aligns with current educational trends, as it promotes the principles of inclusivity, partnership, and interdisciplinary collaboration. Unlike international practice, where co-teaching typically involves a partnership between a teacher and a special educator, in Ukrainian educational institutions it is mostly implemented through the collaboration of a teacher and a teacher assistant. The teacher assistant’s main role is to support the teacher, facilitate individualized learning, adapt materials to students’ needs, and ensure a comfortable inclusive environment, while monitoring progress and providing additional support to enhance educational effectiveness. The results of an empirical study on teachers’ awareness of and attitudes toward co-teaching are presented; the application of co-teaching models in Ukrainian educational institutions, as well as existing organizational and pedagogical challenges requiring systematic solutions, are analyzed. The study indicates that while most teachers and specialists value co-teaching for enhancing collaboration, they face challenges such as limited planning time, low involvement of assistants or special educators, and uncertainty in using effective teaching strategies. Methodological recommendations developed during the study are proposed to enhance the effectiveness of coteaching implementation, optimize collaboration between teachers and assistants, and create a supportive inclusive environment for students with special educational needs.
Specific features of implementing co-teaching in an inclusive educational environment
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: інклюзія; спільне викладання; модель спів-викладання; діти з особливими освітніми потребами (ООП); асистент вчителя; спеціальний педагог